Stigmatisering van patiënten met AIDS, longkanker, syfilis en tubercolose - Peters, L.; den Boer, D.J.; Kok, G.J. (Maastricht : Rijksuniversiteit Limburg, 1989)
Fonds Suzan Daniel (FSD)
Nederlands
Monografie